Role of nitrogen doping on the performance of carbon nanotube catalysts: a catalytic wet peroxide oxidation application - Martin-Martinez, Maria (2016)
Four magnetic carbon nanotube samples (CNTs: undoped, completely N-doped and two selectively N-doped) have been synthesized by chemical vapor deposition. The materials were tested in the catalytic wet peroxide oxidation (CWPO) of highly concentrated 4 nitrophenol solutions (4-NP, 5 g L-1). Relatively mild operating conditions were considered (atmospheric pressure, T = 50 ºC, pH = 3), using a catalyst load of 2.5 g L-1 and the stoichiometric amount of H2O2 needed for the complete mineralization of 4-NP. N doping was identified to influence considerably the CWPO performance of the materials. In particular, undoped CNTs, with a moderate hydrophobicity, favor the controllable and efficient decomposition of H2O2 into highly reactive hydroxyl radicals (HO•), thus showing high catalytic activity for 4-NP degradation. On the other hand, the completely N-doped catalyst, fully hydrophilic, favors a quick decomposition of H2O2 into non-reactive O2 and H2O species. The selectively N-doped amphiphilic catalysts, i.e. hybrid structures containing undoped sections followed by N-doped ones, provided intermediate results, namely: a higher N content favored H2O2 decomposition towards non-reactive H2O and O2 species, whilst a lower N content resulted in the formation of HO•, increasing 4-NP mineralization. Catalyst stability and reusability were also investigated by consecutive CWPO runs.